2021
DOI: 10.1161/jaha.120.017543
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Race‐Ethnic Disparities in Door‐to‐CT Time in Acute Ischemic Stroke: The Florida Stroke Registry

Abstract: Background Less than 40% of acute stroke patients have computed tomography (CT) imaging performed within 25 minutes of hospital arrival. We aimed to examine the race‐ethnic and sex differences in door‐to‐CT (DTCT) ≤25 minutes in the FSR (Florida Stroke Registry). Methods and Results Data were collected from 2010 to 2018 for 63 265 patients with acute ischemic stroke from the FSR and secondary analysis was performed on 15 877 patients with intravenous ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Additionally, female sex was significantly associated with prolonged door-in-door-out time. Prior literature has shown that female patients are less likely to receive certain stroke care benchmarks, such as door-to-CT time of 25 minutes or less . Controlling for insurance status partially mitigated these disparities, but further study is warranted to ascertain the underlying causes and to ultimately implement system redesigns to achieve health equity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, female sex was significantly associated with prolonged door-in-door-out time. Prior literature has shown that female patients are less likely to receive certain stroke care benchmarks, such as door-to-CT time of 25 minutes or less . Controlling for insurance status partially mitigated these disparities, but further study is warranted to ascertain the underlying causes and to ultimately implement system redesigns to achieve health equity.…”
Section: Discussionmentioning
confidence: 99%
“…Patient demographics, including fixed categories for race and ethnicity were extracted from the medical record for inclusion in the registry. These variables were included as racial and sex disparities in other aspects of stroke identification and care have been well described in the literature . Patient risk factors included history of hypertension, diabetes, dyslipidemia, atrial fibrillation, prior stroke, prior TIA, prosthetic heart valve, coronary artery disease or myocardial infarction, carotid artery stenosis, peripheral vascular disease, heart failure, and smoking.…”
Section: Methodsmentioning
confidence: 99%
“…This contrasts with previous studies demonstrating differences in treatment time associated with race and ethnicity. 12,21,22 However, our study demonstrates that systemic disparities still exist with pre-hospital factors at the hospital level. Patients presenting to CHs first had less likelihood of stroke activation and longer DTN time (though they had shorter DTC time).…”
Section: Discussionmentioning
confidence: 66%
“…This contrasts with previous studies demonstrating differences in treatment time associated with race and ethnicity. 12,21,22…”
Section: Discussionmentioning
confidence: 99%
“…In the hospital setting, socioeconomic disparities exist for patients with stroke in terms of access to treatment [11,15,16]. Additionally, variability in stroke imaging utilization on the basis of age, sex, race, and insurance type has been reported [12,[22][23][24][25]. Furthermore, disadvantaged socioeconomic groups have historically been the last to benefit from newer medical technologies [26].…”
Section: Introductionmentioning
confidence: 99%